Federal Republic of Nigeria: Annual Abstract of Statistics 1987 Edition - Federal Office of Statistics, Lagos, Nigeria (Lagos, 1987)
The book contains the economic data of Nigeria from inception up to 1986. it is part of the effort of Federal Office of Statistics (F.O.S), to furnish the public with available information about the economy.
usc 17/08/2021
Ref.
Keywords: Nigeria